Family Attitudes Influence on the Prognosis of Problem Gambling - Fan, (Bernard) Wai Shing (Curtin University, 2023)
This study proposed a new model of gambling relapse, based on a qualitative and quantitative examination of the role of significant others in motivation to quit and relapse. The analyses of reports from significant others supported the hypothesis that families’ attitudes towards problem gamblers may have a supportive or non-supportive influence on their prognosis of gambling addiction.